Communication and patient safety culture in the hospital environment: vision of multiprofissional team - Cristina Daiana Bohrer; Luis Guilherme Sbrolini Marques; Raissa Ottes Vasconcelos; João Lucas Campos de Oliveira; Anair Lazzari Nicola; Andressa Morello Kawamoto (Universidade Federal de Santa Maria, 2016)
Aim: To analyze the patient safety culture regarding communication in view of hospital multidisciplinary team. Method: cross-sectional, descriptive, quantitative research. After employment eligibility. Seventy one professionals of multiple functions / formations from a public teaching hospital of Paraná participated. They responded to the questionnaire "Hospital Survey on Patient Safety Culture". Descriptive statistical analysis proceeded on the items that best depict the patient safety culture regarding communication. Results: there was a good perception of teamwork and internal communication within the unit of work. However, with greater expressiveness, there was unfavorable safety culture regarding communications and activities with external teams to the labor sector as well as weaknesses in passing duty. Conclusions: there is need to increase the communication between different units in the hospital organization, in addition to measures that result in improvements in sectors shift sections